Quid nunc - Stanonik, Bojan (Geodetski vestnik, 1998)
This paper states the case for the need for using managerial knowledge and skills in public/state administration. In addition, the use of the principles of the so-called New Public Management strategy is the primary source of possibility and opportunities for the development of geodesy in the sense of greater public good. It seems evident that new public management is an appropriate solution to the question of quid nunc (What now?)
Keywords: geodezija; management; upravljanje